ANALISIS KRITIS PERKEMBANGAN BSI PASCA MERGER - Kamiliyah, Nuril (IAIN PONOROGO, 2023)
Bank Syariah Indonesia is the result of a merger of 3 Islamic banks which aims to improve Sharia finance in Indonesia. This merger is expected to be able to provide a new choice of financial institutions for the community as well as being able to encourage market share growth in Islamic Banks. In addition, this bank is also expected to become a global player in Islamic banking considering that Indonesia has great potential in realizing this. After the merger has been running for less than 3 years, it is necessary to see the effectiveness of BSI's presence for the development of Indonesian Islamic banking. Both in terms of concrete steps to realize the motivation for the merger, as well as by looking at its financial performance. This research uses a descriptive qualitative method to describe the effectiveness of BSI for Islamic banking in Indonesia, with a library research analysis approach related to the study of the object of this research. The result of the research is within a period of 3 years BSI took various steps to realize the motivation for the bank merger, one of which was by increasing the products offered so that they could reach the Indonesian people more broadly. BSI's financial performance based on ROA and ROE ratio analysis can also be categorized as healthy, with fluctuating developments from the beginning of its establishment. This shows BSI's effective steps for the development of Islamic banking in Indonesia.